GLOBAL EXPERIENCE OF GREEN FINANCING AND POSSIBILITIES OF ITS IMPLEMENTATION IN UZBEKISTAN (International journal of artificial intelligence, 2025)
This article analyzes global experience in green finance, its development, stages of development, and mechanisms for its application. It examines the economic and environmental effectiveness of financial instruments such as green bonds, green loans, and carbon markets, using examples of their successful implementation in developed and developing countries. Based on international experience, practical proposals are developed that can be applied in our country, and prospects for achieving sustainable development goals through green finance are highlighted.